2018
DOI: 10.1002/oby.22345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Versus Continuous Energy Intakes on Insulin Sensitivity and Metabolic Risk in Women with Overweight

Abstract: Objective: This study aimed to compare intermittent fasting (IF) versus continuous energy intakes at 100% or 70% of calculated energy requirements on insulin sensitivity, cardiometabolic risk, body weight, and composition. Methods: Women with overweight (n = 88; 50 ± 1 years, BMI 32.3 ± 0.5 kg/m 2 ) were randomized to one of four diets (IF70, IF100, dietary restriction [DR70], or control) in a 2:2:2:1 ratio for 8 weeks. IF groups fasted for 24 hours after breakfast on three nonconsecutive days per week. All fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
163
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(173 citation statements)
references
References 43 publications
8
163
1
1
Order By: Relevance
“…There has been limited research into IER in patients suffering from metabolic syndrome, and the majority concerns obesity or overweight subjects. According to a study in which there was intermittent fasting versus continuous energy intake at 100% or 70% of requirements on insulin sensitivity, cardiometabolic risk, and body composition in metabolic risk in women with overweight, a 70% energy restriction fasting diet displayed greater reductions in fat mass, weight, cholesterol, and LDL values compared with continuous 70% energy restriction or eucaloric fasting [ 31 ]. Chow et al (2019) investigated the effects of a 12-week time-restricted diet (ad libitum intake during an 8-h eating window) on body composition and metabolic measure in subjects who are overweight and obese.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been limited research into IER in patients suffering from metabolic syndrome, and the majority concerns obesity or overweight subjects. According to a study in which there was intermittent fasting versus continuous energy intake at 100% or 70% of requirements on insulin sensitivity, cardiometabolic risk, and body composition in metabolic risk in women with overweight, a 70% energy restriction fasting diet displayed greater reductions in fat mass, weight, cholesterol, and LDL values compared with continuous 70% energy restriction or eucaloric fasting [ 31 ]. Chow et al (2019) investigated the effects of a 12-week time-restricted diet (ad libitum intake during an 8-h eating window) on body composition and metabolic measure in subjects who are overweight and obese.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this type of practice in intermittent fasting types is promising in terms of cardiometabolic health due to its compatibility with the human circadian rhythm [ 35 ]. The dual-energy X-ray absorptiometry method has been used in many studies investigating the effectiveness of intermittent fasting diets in body weight management [ 31 , 32 ]. In this study, the bioelectric impedance method was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another form of dietary restriction that has gained attention in recent years is alternate‐day fasting (ADF) . ADF regimens generally consist of an ad libitum “feast day” alternated with a 25% energy intake “fast day.” Accumulating evidence has suggested that ADF and CR produce similar weight loss (6%‐8%) over 2 to 12 months in healthy adults with overweight and obesity . Research has also indicated that both diets are safe and well tolerated .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some studies have shown that IF can improve metabolic health and physiological function in humans. IF reduced fat mass, lean mass, and body weight in healthy humans and obese patients [33,[100][101][102][103][104]. Similarly, IF improved lipid and glucose metabolism, reduced inflammatory response, lowered blood pressure, and improved cardiovascular health [102,[105][106][107][108][109].…”
Section: Dietary Manipulations For Human Applicationmentioning
confidence: 96%